Using a Computer-Based Virtual Environment to Assess Social Cognition in Aging: An Exploratory Study of the REALSoCog Task - Msika, Eva-Flore; Ehrlé, Nathalie; Gaston-Bellegarde, Alexandre; Orriols, Eric; Piolino, Pascale; Narme, Pauline (Frontiers in Psychology, 2022)
Although previous studies have suggested that some component processes of social cognition decline in normal aging, several methodological limitations can be pointed out. Traditional sociocognitive tasks assess processes separately and lack ecological validity. In the present study, the main aim was to propose an integrative social cognition assessment in normal aging using an original computer-based task developed in non-immersive virtual reality. Forty-five young adults (YA) and 50 older adults (OA) were asked to navigate in a simulated city environment and to judge several situations that they encountered. These situations investigated social norms by displaying control or (conventional/ moral) transgressions. Following each situation, the participants were asked several questions in order to assess their ability to make moral judgments, affective and cognitive theory of mind, emotional reactivity and empathy, and the propensity to act in a socially appropriate or inappropriate way. The main results showed (i) a preserved ability to detect moral and conventional transgressions with advancing age; (ii) participants’ preserved cognitive ToM abilities; (iii) an age-related decline in affective ToM, that disappeared when the victim was a senior; (iv) preserved emotional reactivity and emotional empathy in normal aging; (v) an increase in inappropriate behavioural intentions in normal aging. Offering more naturalistic conditions, this new task is an interesting integrative measure of sociocognitive functioning to better reflect social behavior in daily living.